Pengaruh Brand Image dan Kualitas Produk terhadap Loyalitas Mahasiswa Universitas HKBP Nommensen Medan Sebagai Pelanggan KFC Sutomo - Octo I Simanullang; Rianti Simanjuntak; Nia A Rajagukguk; Toman Sony Tambunan (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2025)
This Study Aimed To Describe If The Variable Influence On Product Quality Product Purchasing Decisionskfc Sutomo. Whether Variables Affect The Brand Image Of The Product Purchase Decisions KFC Sutomo.Is The Variable Product Quality And Brand Image Influence The Purchasing Produck KFC Sutomo.The Population In This Study Was Students Whom To Be Buying KFC Sutomo At Fakulty Of A Economics And Business, A Total Of 40 Respondents Using Non-Probability Sampling. Data That Has Met The Validity And Reliability, And Classical Assumption (T Test And F Test) Is Processed To Produce A Regression Equation As Follows: Y = 13,789 + -0,261 X1 + 0,689 X2 Where The Purchasing Loyality (Y), The Qulity Of The Product (X1), And Brand Image (X2). Hypothesis Testing Using T Test Showed That The Variable Quality Of The Products That Have Been Researched Proved No Effect On The Purchasing Decisions, But The Variables That Proved Influential Brand Image On Consumers Purchasing Decisions. Hypothesis Testing Using The F Test Shows That The Variable Quality Of The Product And Brand Image Influence On Purchase Decisions By 22, 7%, While The Remaining 77, 3% Is Influenced By Variables That Are Not Used In This Study.